Design techniques and implementation of an 8-bit 200-MS/s interpolating/averaging CMOS A - Uyttenhove, K. (IEEE Journal of solid state circuits)
The design issues and tradeoffs of a high-speed high-accuracy Nyquist-rate analog-to-digital (A/D) converter are described. The presented design methodology covers the complete flow from specifications to verified layout and is supported by both commercial and internally developed computer-aided design tools. The major decisions to be made during the converter's design at both the architectural and the circuit level are described and the tradeoffs are elaborated. The approach is demonstrated for a real-life test case, where a Nyquist-rate 8-bit 200-MS/s 4-2 interpolating/averaging A/D converter was developed in a 0.35-μm CMOS technology. The signal-to-noise-plus-distortion ratio at 40 MHz is 42.7 dB and the total power consumption is 655 mW.